The Concept of the Manners of Seeking Knowledge in the Story of Prophet Moses and Khidr in the Qur'an (A Study of Interpretation and Perspectives of Islamic Education) - Azizah, Ayunda (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The story of the prophet Musa and khidir in surah al-kahfi verses 60-82 is one of the narrations of the Qur'an which in its verse contains the values of education, especially manners in seeking knowledge. This article aims to examine the concept of manners in seeking knowledge through the analysis of the story and relate it to the relationship of Islamic education today. The method used in literature study is to collect data through books, journals, articles, and related interpretations, with a descriptive analysis approach. The results of the study not only show how the process of seeking knowledge is, but also emphasize the importance of ethics, spirilituality, and patience in learning. These values are in the form of humility, seriousness, obedience to teachers, and the ability not to be too quick in judging something. In today's education, these values can be the basis that is instilled in students so that they become students who are not only intellectually intelligent but also moral and moral students.